Alterations in fecal Lactobacillus and Bifidobacterium species in type 2 diabetic patients in Southern China population - Lê, Kim-Anne; Li, Yan; Xu, Xiaojin; Liu, Tingting; Yang, Wanting; He, Fang; Su, Kuanyuan; Cai, De Hong; Go, Vay Liang W; Pandol, Stephen; Hui, Hongxiang (Frontiers in Physiology, 2013)
Background: The connection between gut microbiota and metabolism and its role in the pathogenesis of diabetes are increasingly recognized. The objective of this study was to quantitatively measure Bifidobacterium and Lactobacillus species, members of commensal bacteria found in human gut, in type 2 diabetic patients (T2D) patients from Southern China. Methods: Fifty patients with T2D and thirty control individuals of similar BMI were recruited from Southern China. T2D and control subjects were confirmed with both oral glucose tolerance test (OGTT) and HbA1c measurements. Bifidobacterium and Lactobacillus species in feces were measured by real-time quantitative PCR. Data were analyzed with STATA 11.0 statistical software. Results: In comparison to control subjects T2D patients had significantly more total Lactobacillus (+18%), L. bugaricus (+13%), L. rhamnosum (+37%) and L. acidophilus (+48%) (P <0.05). In contrast, T2D patients had less amounts of total Bifidobacteria (-7%) and B. adolescentis (-12%) (P <0.05). Cluster analysis showed that gut microbiota pattern of T2D patients is characterized by greater numbers of L. rhamnosus and L. acidophillus, together with lesser numbers of B. adolescentis (P <0.05). Conclusion: The gut microflora in T2D patients is characterized by greater numbers of Lactobacillus and lesser numbers of Bifidobacterium species.